High-Performance Electrode Based on Activated Carbon for Electrochemical Energy Sources - Bakhmatyuk, B.P.; Dupliak, I.Ya.; Voitoviс, J.M. (Наносистеми, наноматеріали, нанотехнології, 2016)
This study shows that ‘Norit DLC Supra 30’ commercial activated carbon material (NS commercial ACM) provides high-performance electrode for electrochemical energy sources (EES) in 25% ZnI2 aqueous electrolyte. This is shown on the basis of the analysis of the desorption isotherms of iodine, the dependences of the specific discharge capacity (Cd) on current load, and the Ragone plot drawn using galvanostatic charge–discharge (GCD) dependences at a current density (i) range of 0.5–9 A∙g⁻¹. High values of fractional surface coverage (θ), from 0.73 to 0.87, determine large values of specific energy (W), from 1240 J∙g⁻¹ to 1096 J∙g⁻¹, at the values of specific power (P) range from 0.6 to 8 W∙g⁻¹. NS commercial ACM shows high values of specific energy (W = 1217 J∙g⁻¹), specific capacitance (Cd = 1156 C∙g⁻¹), Coulomb efficiency ( η = 88%), and specific power (P = 4.3 W∙g⁻¹) in the 2000th cycle.